KONSEP KEPEMIMPINAN DALAM PENDIDIKAN ISLAM: IMPLEMENTASI DAN RELEVANSINYA - Moch Ayub Mustaqim; Azmi Safroni; Siti Patimah; M. Makhrus Ali (Institut Ummul Quro Al-Islami Bogor, 2024)
Leadership in Islamic education is a very important aspect to create an effective and productive learning environment. This study discusses various dimensions of leadership in the context of Islamic education, including the characteristics of a leader, the challenges faced, and strategies that can be applied to improve the quality of education. By using the latest data and statistics, as well as relevant case examples, this study aims to provide a deeper understanding of the role of leadership in advancing Islamic education in Indonesia. It is hoped that the results of this study can be a reference for educators, policy makers, and leaders of educational institutions in improving the quality of education based on Islamic values.